Chronic Massive Fetomaternal Hemorrhage in a newborn from immigrants. Clinical and organizational implications - E. Ruffini; A.M. Bianchi; L. De Petris; M.K. Fares; G. Zorzi; A. Carlucci (PAGEPress Publications, 2012)
Fetomaternal hemorrhage (FMH) refers to the entry of fetal blood into the maternal bloodstream before or during delivery. FMH of more than 30 mL occurs with the frequency of about 1/300. Fetal outcomes may be compromised by still births, hydrops fetalis, cardiac complications, and increased rates of postpartum infant death. In most cases, the cause is not identified. Clinical manifestations of FMH depend on the volume of blood lost and the rate that it occurred. We report a case of chronic massive FMH in a newborn of an immigrant mother with a favorable outcome. Medical visits and tests during pregnancy, including ultrasound scans, were not performed. The baby was hemodynamically stable after birth, manifesting only pallor. The complete blood count revealed severe hypochromic anemia (hemoglobin 3,8 g/dl, hematocrit 14,4%) and reticulocytosis (reticulocyte 25,2%). There was no ABO blood type incompatibility and the result of direct Coomb's test was negative. The Kleihauer-Betke test revealed 5 % of fetal erythrocytes in the maternal bloodstream equivalent to 180 mL. The fact that FMH can occur without prior risk factors, and the diagnosis is often postnatal, underscores the importance of heightened of medical suspicion particularly in infants born to immigrants where there is often the lack of prenatal visits.